Effect of Needle Brand, Needle Bevel Grind, and Silicone Lubrication on Contamination of Joints With Tissue and Hair Debris After Arthrocentesis. Issue 3 (5th April 2014) - Waxman, Sarah J.; Adams, Stephen B.; Moore, George E.
<x xml:space="preserve">Abstract</x> Objective To assess contamination of joints with tissue and hair debris after arthrocentesis. Study Design Experimental. Animals Fetlock joint tissues (n = 6 horses). Methods Soft tissue flaps including joint capsule were dissected from the dorsal aspect of fetlock joints of 6 anesthetized horses leaving an intact proximal base ("live" model) or with complete excision and immediate mounting to a wooden frame ("fresh" model). Needles were inserted through joint tissues and saline solution was flushed through them into tissue culture plate wells, and then examined for tissue and hair debris. Nine needle types were assessed; variables included needle brand, needle bevel grind, needle size, and silicone lubrication. Results No significant difference was detected between "live" and "fresh" models for hair or tissue contamination. Compared to 20g hypodermic needles, 19g lubricated and 19g non‐lubricated needles had a significantly greater odds ratio (OR) for hair contamination. Nineteen‐gauge non‐lubricated needles had a significantly greater OR for hair contamination than 19g lubricated needles. No significant differences in ORs were identified between type of needle bevel grind, brands of disposable hypodermic needles, or brands of spinal needles for hair or tissue contamination. Conclusions Nineteen‐gauge needles significantly increase the risk of joint contamination with hair compared to 20g needles; non‐lubricated 19g needles have the greatest risk. All other needle types tested in this study have similar risks for tissue and hair contamination after arthrocentesis.